Does governance reform help? the impact of split share structure reform on corporate board structure in Chinese manufacturing enterprises - Zhang, C.; Cheong, K.C.; Li, R.; Rasiah, R. (Malaysian Economic Association, 2016)
This study explores the determinants of board size and independence in the Chinese manufacturing industry during the periods before and after the split share structure reform. The results show that with the implementation of the Chinese split share structure reform, corporate governance was impacted positively in terms of the greater board independence. Meanwhile, the mainstream view that non-state enterprises are better governed than state enterprises has found no support. Overall the study suggests that one board size and one type of board independence may not fit all firms under different corporate governance environments.